2004
DOI: 10.1007/s10336-004-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption, body mass and fat deposition in captive regent honeyeaters, Xanthomyza phrygia (Meliphagidae), during the non-breeding season

Abstract: The regent honeyeater (Xanthomyza phrygia) is a large endangered honeyeater from eastern and south-eastern Australia. Little is known about the ecology of this bird during the autumn-winter period, when it is absent from its breeding areas. In this study, food consumption and body condition of captive regent honeyeaters were studied during this period. Nectar was the dominant component of the regent honeyeaters' diet and varied significantly throughout the study, peaking in early July. Fruit and mealworm consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…To encourage natural foraging, favoured flowering trees and shrubs are planted in the aviaries and provided as cut browse when available. Foraging studies at Taronga have shown that body mass and fat deposition in both sexes increase through autumn, which is consistent with other Australian honeyeater species (Munro & McFadden, 2005a).…”
Section: Husbandrysupporting
confidence: 86%
“…To encourage natural foraging, favoured flowering trees and shrubs are planted in the aviaries and provided as cut browse when available. Foraging studies at Taronga have shown that body mass and fat deposition in both sexes increase through autumn, which is consistent with other Australian honeyeater species (Munro & McFadden, 2005a).…”
Section: Husbandrysupporting
confidence: 86%